2016
DOI: 10.1111/apt.13876
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: efficacy and safety of vonoprazan vs. lansoprazole in patients with gastric or duodenal ulcers – results from two phase 3, non‐inferiority randomised controlled trials

Abstract: Summary Background Vonoprazan is a new potassium‐competitive acid blocker for treatment of acid‐related diseases. Aim To conduct two randomised‐controlled trials, to evaluate the non‐inferiority of vonoprazan vs. lansoprazole, a proton pump inhibitor, for treatment of gastric ulcer ( GU ) or duodenal ulcer ( DU ). Methods Patients aged ≥20 years with ≥1 endoscopically‐confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
85
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 17 publications
5
85
1
Order By: Relevance
“…The pharmaceutical advantages of P-CAB over PPIs include more rapid, stronger and longer-lasting inhibition of gastric acid secretion after administration [7,15,16]. For the treatment of peptic ulcers, Miwa et al reported that a 20 mg dose of vonoprazan had a similar tolerability profile as a 30 mg dose of lansoprazole, and was not inferior to lansoprazole with respect to gastric ulcer healing [17]. The relative effectiveness of vonoprazan compared to PPIs for the management of artificial ulcers after ESD remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmaceutical advantages of P-CAB over PPIs include more rapid, stronger and longer-lasting inhibition of gastric acid secretion after administration [7,15,16]. For the treatment of peptic ulcers, Miwa et al reported that a 20 mg dose of vonoprazan had a similar tolerability profile as a 30 mg dose of lansoprazole, and was not inferior to lansoprazole with respect to gastric ulcer healing [17]. The relative effectiveness of vonoprazan compared to PPIs for the management of artificial ulcers after ESD remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…But within the studies involved, treatment duration was different; two studies just observed the results at 2 weeks after ESD, and others were at 4 weeks at least. Treatment duration is known to be an extremely important factor for ulcer healing; longer treatment duration leads to more complete healing . Subgroup analysis in our study, after excluding the two studies with short treatment duration, showed that pooled MD of the remaining studies (with treatment durations of at least 4 weeks) was 0.26 ( P = 0.008).…”
Section: Discussionmentioning
confidence: 59%
“…A systematic review and meta‐analysis has shown that triple therapy with vonoprazan as the acid inhibitor had superior efficacy in terms of H. pylori eradication compared with the triple therapy including PPIs . Studies have also shown a better potential capacity of vonoprazan to heal benign ulcers such as peptic ulcers and nonsteroidal anti‐inflammatory drugs (NSAIDs)‐induced ulcers . Kagawa et al reported a better efficacy of vonoprazan in reducing the risk of post‐ESD bleeding compared with PPIs (1.3% vs 10%), at the same time vonoprazan had a higher ulcer shrinkage rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the intragastric pH following VPZ treatment (pH 5.2) has been identified to be significantly higher than that following esomeprazole treatment (pH 3.0) on day 1 of therapy (18). The superior efficacy of VPZ compared with PPIs has been reported in various gastrointestinal diseases (19)(20)(21)(22).…”
Section: Eradication Rate % (N) -------------------------------------mentioning
confidence: 99%